Accumulation and distribution of trace metals within soils and the austral cordgrass Spartina densiflora in a Patagonian salt marsh - Idaszkin, Yanina Lorena (2015)
Concentrations of Cd, Cu, Fe, Pb, and Zn were determined in soils and in below- and above-ground structures of Spartina densiflora in a Patagonian salt marsh (San Antonio, Río Negro, Argentina). Also, the relationship between trace metal concentrations in soils and plants was investigated to improve our knowledge regarding the ability of this plant species to take up and accumulate trace metals from the soil. Our results indicate that, within the studied salt marsh, soil trace metal concentrations follow a decreasing concentration gradient toward the sea. They show moderate pollution and a potentially negative biological effect in one site of the salt marsh. While below-ground structures reflect the soil metal concentration pattern, this is not so evident in above-ground concentrations. Also, S. densiflora is able to absorb a limited amount of metals present in the soil, the soil bioaccumulation factor being lower in sites where soil metal concentration is higher.